Omega‐3 supplementation during pregnancy to prevent recurrent intrauterine growth restriction: systematic review and meta‐analysis of randomized controlled trials. (4th November 2015) - Saccone, G.; Berghella, V.; Maruotti, G. M.; Sarno, L.; Martinelli, P.
ABSTRACT: Objective: To evaluate the efficacy of omega‐3 supplementation during pregnancy in preventing intrauterine growth restriction (IUGR) in women with apparently uncomplicated singleton pregnancy and previous IUGR pregnancy. Methods: For this systematic review, the research protocol was designed a priori . Searches were performed in electronic databases for studies published from inception of each database to December 2014. A combination of search terms was used including 'fish oil', 'long chain polyunsaturated fatty acids', 'intrauterine growth restriction', 'small for gestational age' and 'omega‐3'. We included all randomized controlled trials (RCTs) of women with an uncomplicated singleton pregnancy and a prior IUGR pregnancy who were randomized to receive prophylactic treatment with omega‐3 supplementation or either placebo or no treatment (control). Trials that included women with multiple gestations and those with only biochemical outcomes available were excluded. Pooled estimates were based on relative risk (RR) with 95% CI. Primary outcome was incidence of IUGR as defined in the RCTs. Results: Three RCTs including 575 women with uncomplicated singleton pregnancy with prior IUGR were analyzed. Women who received omega‐3 supplementation during pregnancy had the same incidence of IUGR, defined as estimated fetal weight < 5 th or < 3 rd centiles, as had controls (22.8% vs 20.2%, respectively; RR, 1.13 (95% CI, 0.83–1.54)). Compared to controls, women who received omega‐3 supplementation delivered later (mean difference, 1.4 (95% CI, 1.28–1.63) weeks), had a longer latency (mean difference, 2 (95% CI, 1.73–2.08) weeks), had a similar incidence of perinatal death (2.1% vs 3.3%, respectively; RR, 0.60 (95% CI, 0.15–2.42)) and similar birth weight (mean difference, 50 g (95% CI, −26 to 246 g)). Conclusions: Omega‐3 supplementation during pregnancy does not prevent recurrence of IUGR in women with uncomplicated singleton pregnancy and a previous IUGR pregnancy. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.